Diagnostic Value of Proenkephalin A 119 – 159 Serum in Early Detection of Sepsis Associated Acute Kidney Injury - Wahyudi, Adefri; Priyono, Drajad; Harun, Harnavi; Viotra, Deka; Najirman, Najirman; Kurniati, Roza; Simajuntak, Rohayat Bilmahdi; Murni, Arina Widya (PERNEFRI (PERHIMPUNAN NEFROLOGI INDONESIA), 2026)
Background: Sepsis asscociated acute kidney injury (SA-AKI) is common condition that found in sepsis. Due to the lack of creatinine serum, this condition possibly makes therapy delayed. Proenkephalin A 119-159 (PENK) is a breakdown product of the prohormone proenkephalin A which freely filtered at the glomerulus. In other hand, this prohormone and its receptor predominantly expressed in proximal Tubular Epythelial Cells (pTEC) of kidney. Elevated serum PENK levels are an indicator of AKI. However, previous studies have shown varies results. Objectives: This study aims to determine early detection biomarkers for the presence of AKI in sepsis. Methods: This diagnostic test was conducted at Dr. M. Djamil General Hospital Padang in sepsis patients. The diagnosis of AKI was established based on the 2012 KDIGO criteria. Results: The study involved 98 sepsis patients, 58.16% (n=57) of them experienced AKI. Serum creatinine levels at admission and within 48 hours of hospitalization were 1.0 (IQR 0.8–1.5) mg/dl and 1.6 (IQR 0.9–2.1) mg/dl, respectively. A serum PENK level ≥82.6 pmol/L at admission had sensitivity of 98.6%, specificity of 95.1%, positive predictive value of 96.1%, negative predictive value of 97.5%, and accuracy of 96.9% in early detection of AKI in sepsis. Conclusion: Serum PENK level has excellent diagnostic value in early detection of AKI in sepsis.